Odpowiedzi

2009-10-04T16:09:39+02:00
A) -7(x+2)+4=3x
-7x-14+4=3x
-14+4=3x-7x
-10=-4x/: -4
2,5=x


d) 2x(x-1)=2(x-1)(x+2)
3x-2x=(2x-2)(2x+4)
x=4x+2
-3x=2/ : -3
x= -2/3



2009-10-04T16:11:16+02:00
-7(x+2) +4= 3x
-7x-14+4=3x
-10x=10 |:-10
x=-1

1- 2x+5/3= 4 |*3
1-2x+5=12
-2x=6 |:-2
x=-3

-4 (1/2x-2) -4 = 2(-x + 2)
-2x+8-4=-2x+4
0=0
Równanie tożsamościowe

2x(x - 1) = 2(x - 1)(x + 3)
2x<kw>-2x=2(x<kw>+2x-3)
2x<kw>-2x=2x<kw>+4x-6
-6x=-6 |:-6
x=1

x/2 - x/3 + 1 = 1/6 (x + 6) |*6
3x-2x+1 = x+6
0=5
Równanie sprzeczne

x-1/ 4 - x+1 / 2 = - x/ 4 |:4
x-1-2x+2=-x
0=3
Równanie sprzeczne

1 5 1
2009-10-04T16:11:56+02:00
A)-7x-14 + 4 =3x
-7x -3x=14-4
-10x=10 / :(-10)
x=-1
b)1- 2x+5/3= 4
-2x=4-1-5/3
-2x=3-5/3
-2x=-4,6 /:(-2)
x=2,3
c)-4 (1/2x-2) -4 = 2(-x + 2)
-2x + 8 -4 = -2x + 4
-2x + 2x= 4+4 -8
0=0